Cultural practices, healthcare-seeking behaviors, and wildlife interface: Zoonotic disease risks among the Phu Thai Ethnic Group in Thailand - Nisachon Bubpa; Kanokwan Suwannarong; Kannika Thammasutti; Thanomsin Ponlap; Worakamon Thongkan; Paisit Boonyakawee; Phitsanuruk Kanthawee; Kangsadal Suwannarong; Withaya Chanchai (Veterinary World)
Background and Aim: Emerging infectious diseases, with 75% originating from zoonotic sources, highlight the interconnectedness of human, animal, and environmental health. The coronavirus disease 2019 (COVID-19) pandemic underscored the importance of the One Health (OH) approach, especially in rural and ethnic communities where cultural practices and wildlife interactions may amplify zoonotic disease risks. This study determined the healthcare-seeking behaviors and wildlife interface of the Phu Thai ethnic group in Mukdahan Province, Thailand, to understand their cultural practices, zoonotic disease risks, and pandemic-related adaptations.